Pollen Developmental Arrest: Maintaining Pollen Fertility in a World With a Changing Climate - Pacini, Ettore; Dolferus, Rudy (Frontiers in Plant Science, 2019)
During evolution of land plants, the haploid gametophytic stage has been strongly reduced in size and the diploid sporophytic phase has become the dominant growth form. Both male and female gametophytes are parasitic to the sporophyte and reside in separate parts of the flower located either on the same plant or on different plants. For fertilization to occur, bi-cellular or tri-cellular male gametophytes (pollen grains) have to travel to the immobile female gametophyte in the ovary. To survive exposure to a hostile atmosphere, pollen grains enter a state of complete or partial developmental arrest (DA), a reversible state of desiccation that protects them against environmental injuries. DA in pollen is poorly understood and depends on the plant species and its mode of pollination. DA is also strongly influenced by the reigning environmental conditions at the time of pollen dispersal. Environmental stresses frequently induce pollen sterility and reduced productivity in many crop species. It is therefore important to gain a better understanding about how DA and pollen viability is controlled and how it is affected by the environment. This paper provides an overview of what is known and where knowledge is lacking.